Anti-Hiv Potential Of Medicinally Important Plants - RAJANDEEP KAUR,; RAJEEV KHARB, (International Journal of Pharma and Bio Sciences, 2011)
The acquired immunodeficiency syndrome (AIDS) is a result of human immunodeficiency virus (HIV) infection which leads to severe suppression of immune functions. AIDS is a real threat to the health of mankind, and the search for effective therapies is still of great importance. However besides the high cost, there are adverse effects and limitations associated with chemotherapy applied. Thus herbal medicines are frequently used as an alternate therapy by individuals living with HIV. Numerous plant derived compounds have been evaluated for inhibitory effects on HIV replication, and many have been found to inhibit different steps in HIV replication cycle. The aim of this review is to list research findings for herbal medicines which are endowed with the ability to inhibit HIV.